Antibacterial Effect of Mentha spicata Essential Oil on Listeria monocytogenes in Traditional Lighvan Cheese. Issue 4 (16th October 2013) - Moosavy, Mir‐Hassan; Esmaeili, Saber; Mostafavi, Ehsan
<x xml:space="preserve">Abstract</x> Abstract Listeria monocytogenes is a foodborne pathogen that is widespread in the environment. There are several reports on the isolation of L. monocytogenes from many types of cheeses. The aim of this study was to evaluate the antibacterial effect of Mentha spicata essential oil on L. monocytogenes in traditional Lighvan cheese. L. monocytogenes was added to the raw ewe's milk and M. spicata essential oil was subsequently mixed with the milk at concentrations of 0, 2 and 2.5%. After producing the cheese, sampling performed until 60 days. Results of this study showed that M. spicata essential oil at all concentrations was effective against L. monocytogenes in comparison with the control group (P < 0.001). There was no significant difference between 2 and 2.5%. Effect of the M. spicata essential oil on L. monocytogenes at 14C was greater than 4C. Also, with increasing salt water concentration, the anti‐Listerial effect of the M. spicata essential oil increased. Practical Applications These findings may be of significant importance with regard to food safety because application of M. spicata essential oils for control of L. monocytogenes in unpasteurized and traditional cheeses tested and achieved best results. Also, environmental conditions (NaCl and temperature) increased antibacterial effect of M. spicata in cheese.